Opposition ved forsvarshandlingen af Bent Christensens disputats: Omkring Grundtvigs Vidskab - Jørgensen, Theodor (Grundtvig-Studier, 1999)
From the Public Defence of Bent Christensen’s Dissertation for the Doctorate, »About Grundtvig ’s Vidskab« By Theodor Jørgensen By way of introduction, the thesis of the dissertation is briefly presented, viz. that, according to Grundtvig, the commitment to life inherent in the Christian faith has a cognitive aspect which he develops in a universal-historical vidskab view, but which he later abandons - if not in principle, at least in reality - in favour of a concentration on his church programme on one hand and his programme for the enlightenment of the people on the other. According to Bent Christensen, the reason was of an apologetic and strategic character in that Grundtvig wanted to overcome the isolation in which he found himself in his relations with his age in his first long phase of work. This thesis is partially contested in the article. As an objective reason for this development it is pointed out that Grundtvig recognized the unattainableness of a united Christian culture and prepared himself for the pluralism of modernity. This rendered it necessary to seek out the possibility for interaction between people with different opinions in essential areas of popular life as well as Christian life. This is why the idea of freedom plays an increasingly important role for Grundtvig. His thinking moves more and more in an elliptic direction with the universal and the local or particular as the two focal points. It is true that the two focal points are sometimes brought into relation with each other by means of the notion of the Chosen People, in which there is an inherent danger of an ethnocentric nationalism which Grundtvig does not always escape. The article further points to the necessity of a study of Grundtvig’s attitude to the theories of science of his age. An immanent interpretation such as that presented in Bent Christensen’s dissertation is not sufficient.